Which patient and doctor behaviours make a medical consultation more effective from a patient point of view. Results from a European multicentre study in 31 countries. Issue 10 (October 2018) - Mazzi, Maria Angela; Rimondini, Michela; van der Zee, Egbert; Boerma, Wienke; Zimmermann, Christa; Bensing, Jozien
Highlights: Assessments of patient views on how doctors and patients can improve communication. Representative samples of primary care patients from 31 European countries. Multilevel exploration of the joint contribution of patient and country information. Being treated as a person and partner is universally considered of great importance. Patients attribute more responsibility to doctors for a more effective consultation. Abstract: Objective: To assess European patients' preferences regarding seven aspects of doctor-patient communication. Methods: 6049 patients from 31 European countries evaluated 21 doctor and 12 patient behaviours, through a patient-generated questionnaire (PCVq). Multilevel models explored the effects of patient characteristics, contextual and cultural dimensions on preferences. Results: Patients attributed more responsibility to doctors, by giving greater importance to doctor than to patient factors, in particular to Treating the patient as a partner and as a person and Continuity of care . Gender, age, education, the presence of chronic illness and two of Hofstede's cultural dimensions, Individualism and Indulgence, showed differential evaluations among patients. Women gave greater importance to all seven communication aspects, older patients to being prepared for the consultation, lower educated patients to Treating patient as a person and Thoughtful planning. Patients from countries with an indulgent background rated all seven communication aspects of greater importance. A more individualistic orientation was related to lower importance regarding the four doctor's factors and the patient factor Open and Honest. Conclusions: Treating the patient as a person and providing continuity of care emerged as universal values. Practice implications: The findings should represent a landmark for the adaptation of patient-generated communication guidelines and programs in Europe.